2004
DOI: 10.1007/s00280-003-0719-4
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and tumor disposition of platinum after administration of cisplatin or STEALTH liposomal-cisplatin formulations (SPI-077 and SPI-077 B103) in a preclinical tumor model of melanoma

Abstract: This study suggests that more SPI-077 and SPI-077 B103 distribute into tumors, but release less Pt into tumor ECF, and form fewer Pt-DNA adducts than does cisplatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
99
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(106 citation statements)
references
References 31 publications
6
99
0
1
Order By: Relevance
“…By microdialysis, we were previously unable to detect released platinum (Pt) in tumor ECF after administration of STEALTH liposomal cisplatin (SPI-077; ref. 18). The results of this study suggested that SPI-077 distributes into tumors but release less unbound Pt into tumor ECF and form fewer Pt-DNA adducts as compared with cisplatin, which was consistent with low antitumor activity of SPI-077 (18).…”
supporting
confidence: 67%
See 1 more Smart Citation
“…By microdialysis, we were previously unable to detect released platinum (Pt) in tumor ECF after administration of STEALTH liposomal cisplatin (SPI-077; ref. 18). The results of this study suggested that SPI-077 distributes into tumors but release less unbound Pt into tumor ECF and form fewer Pt-DNA adducts as compared with cisplatin, which was consistent with low antitumor activity of SPI-077 (18).…”
supporting
confidence: 67%
“…Liposomes extravasate through leaky capillary beds of tumors and lodge into the interstitial spaces among tumor cells, where they release the encapsulated drug (6, 16 -18). For anticancer agents encapsulated in liposomes to be an effective treatment in patients with solid tumors, the active form of the anticancer agent must be released from the liposome into the tumor ECF and then penetrate into the cell (6,18).…”
mentioning
confidence: 99%
“…However, there was a poor therapeutic effect in three murine tumor models owing to the slow release rate of cisplatin from liposomes. A similar result was observed by Zamboni et al (2004) after mice bearing melanoma tumors were administered cisplatin loaded PEG-modified liposomes.…”
Section: Pegylated Liposomal Vincristinesupporting
confidence: 69%
“…However, in Phase I and II studies, SPI-077 exhibited essentially no antitumor activity in patients [42][43][44]. A subsequent study in tumor-bearing mice indicated that although more SPI-077 distributes into tumors, it releases less Pt into the tumor, and forms fewer Pt-DNA adducts, as compared with free cisplatin [45].…”
Section: Liposomal Formulations Of Platinum Drugsmentioning
confidence: 99%